2021
DOI: 10.1002/deo2.51
|View full text |Cite
|
Sign up to set email alerts
|

Novel clip device for prevention of bleeding after endoscopic papillectomy

Abstract: Objectives Recently, a novel clip device, SureClip ® (Micro‐Tech Co. Ltd., Nanjing, China), has been developed, which improved rotation and reopening performance. We aimed to assess the efficacy of the SureClip ® in prophylactic closure of the mucosal break after endoscopic papillectomy (EP) for ampullary neoplasm. Methods We retrospectively reviewed the medical records of 40 patients who underwent EP for ampullary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…9 novel endoscopic clip devices with rotation, reopening, and repeated repositioning tions has been developed, and several recent studies have demonstrated the effectiveness of these novel clip devices for preventing delayed bleeding after EP. 10,15 In this study, we used a novel clip device in our VIO-EP group. As shown in Table 4, a bleeding point below the papilla was less common in the VIO-EP group with a novel clip device than in the ICC-EP group with the conventional clip device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 novel endoscopic clip devices with rotation, reopening, and repeated repositioning tions has been developed, and several recent studies have demonstrated the effectiveness of these novel clip devices for preventing delayed bleeding after EP. 10,15 In this study, we used a novel clip device in our VIO-EP group. As shown in Table 4, a bleeding point below the papilla was less common in the VIO-EP group with a novel clip device than in the ICC-EP group with the conventional clip device.…”
Section: Discussionmentioning
confidence: 99%
“…The value of preventive closure of the frenulum by clipping has been reported to reduce delayed bleeding after EP 9 . Furthermore, novel endoscopic clip devices with rotation, reopening, and repeated repositioning functions has been developed, and several recent studies have demonstrated the effectiveness of these novel clip devices for preventing delayed bleeding after EP 10,15 . In this study, we used a novel clip device in our VIO‐EP group.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding from the tumor is difficult to stop endoscopically, and cases of vascular embolization and irradiation have been reported 2,3 . Recently, reopenable clips have been effective for uncontrolled bleeding in gastric endoscopic submucosal dissection 4 and prevention of bleeding after endoscopic papillectomy 5 . With a single reopenable clip, hemostasis can be confirmed before final deployment and be reliably achieved even in difficult cases.…”
Section: Brief Explanationmentioning
confidence: 99%
“…Duodenoscopic clipping is often challenging because the duodenoscope elevator may disrupt the opening and rotation of the clip. However, the SureClip (Micro-Tech Co. Ltd., Nanjing, China), which provides enhanced rotational and re-opening performance, facilitates easier clipping while using a duodenoscope 1 . Recently, a novel clip-band device called the SureClip Traction Band (Micro-Tech Co. Ltd.) was developed and reported to be a useful traction device for endoscopic submucosal dissection 2 .…”
Section: Figmentioning
confidence: 99%